Parenchymal Hemorrhage Rate Is Associated with Time to Reperfusion and Outcome. Issue 5 (24th August 2022) - Olivot, Jean‐Marc; Finitsis, Stephanos; Lapergue, Bertrand; Marnat, Gaultier; Sibon, Igor; Richard, Sebastien; Viguier, Alain; Cognard, Christophe; Mazighi, Mikael; Gory, Benjamin; ,
Abstract : Objective: Despite a 90% reperfusion rate, only 50% of patients with anterior circulation large vessel occlusion‐related acute ischemic stroke (LVO‐AIS) have a functional recovery at 3 months. Parenchymal hematoma (PH) is a predictor of poor outcome after endovascular treatment (EVT). We aim to investigate the relationship between the delay from onset to reperfusion, the occurrence of PH, and functional outcome. Methods: The Endovascular Treatment in Ischemic Stroke (ETIS) registry is an ongoing prospective observational study. Data were analyzed from the subgroup of patients who underwent a successful EVT defined by a modified Thrombolysis in Cerebral Infarction (mTICI) score 2b‐3. We assessed the factors associated with PH, (ie, PH1 or PH2 grade according to the European Collaborative Acute Stroke Study 2 (ECASS) classification of hemorrhagic transformation), then evaluated the relationships between PH, delay from onset to reperfusion, and functional recovery defined by a modified Rankin Scale (mRS) of 0–2. Results: We analyzed 2, 919 patients with an LVO‐related AIS who underwent a successful EVT. Overall, 13.3% of the participant experienced a PH. The rate of PH increased by 2.5% (95% CI 1.5%–3.6%, p < 0.001) for every additional hour of onset to reperfusion delay and was, by comparison with the other study patients, consistently associated with a lower rate of functional recovery 19.7% (95% CI 11.6%–27.7%, p < 0.001) irrespective of time from onset to reperfusion. Interpretation: Our results demonstrate that PH rate is associated with the delay from onset to reperfusion and participates in the relationship between time to reperfusion and outcome. Time is Bleeding. ANN NEUROL 2022;92:882–887